Rome à la campagne : les décors en pierre de la villa de la Grande Boussue à Nouvelles (Mons, Belgique) - Catherine Coquelet; Roland Dreesen; Éric Goemaere; Éric Leblois; Marie-Thérèse Raepsaet-Charlier (Gallia)
The remains of the Nouvelles villa (Mons, Belgium) were discovered by Émile de la Roche de Marchiennes at the end of the 19th century. They extend over at least six hectares and were investigated during eighteen excavation campaigns between 1964 and 1985. This rural settlement was built in the Nervian civitas, 16 km away from Bavay. A Protohistoric occupation was followed in the first half of the 1st century AD by a settlement bordered by a great rectangular enclosure of almost two hectares. At the beginning of the 2nd century a very large aristocratic residence was built with a 1.5 km long aquaduct and baths. After a final transformation and embellishment at the end of the 2nd or beginning of the 3rd century, this main building reached a length of almost 300 metres. In the last third of the 3rd century, a violent fire destroyed the villa which was subsequently abandoned.In addition to 2628 pieces of decorative stones, several fragments of mosaics including 1570 tesserae were collected during these excavations. Belgian stones are predominantly present: Devonian and Carboniferous grey-blue limestones, various Belgian marbles including the Gris des Ardennes and the Rance red marble, as well as clayey limestones of the Tournai stone type. Two magmatic rocks originate from Germany: the Berkum trachyte and the Trier diabase. A few coloured stones originate from France such as the Pouillenay limestone and the Campan marble (both the green and pink varieties). Architectural decorations are made in Euville stone, a white limestone from Lorraine, mainly used in the neighbouring town of Tongres, and above all, in Avesnes stone, a variety of white chalk not only used in Bavay but also in the urban settlement of Famars. Nevertheless, additional Mediterranean stones, present in very small quantities, allow the development of a wider range of colours.The richest collection of ornamental stones comes from a 36 m2 heated room located in the southern wing of the settlement. It shows a black and white floor mosaic imitating an opus sectile. In the fire and demolition layers some remains of paintings were found as well as stucco and especially, 1479 fragments of stones belonging to its wall revetments.The most remarkable pieces are the crustae in Giallo antico, white Mediterranean marble (Carrara?) and Rosso antico. They resemble the acanthus frieze pattern of a luxurious room in a 4th-century domus near the Porta Marina in Ostia. In northern Gaul, a few analogous fragments have been found in the 2nd-3rd century domus discovered during excavations in the Notre-Dame basilica in the capital of Tongeren (Belgium), in the 4th-century basilica of Trier and in the wall revetments of the Palatiolum (in Pfalzel, Germany). Other objects are also composed of regional decorative stones, such as pieces cut in the white parts (fossil corals) of red Rance marble slabs. Another slab made of Meuse stone clearly shows a leaping animal (feline?).This room was embellished with a stone decoration extending over an important height (marble veneer). Sawn slabs in Gris des Ardennes and Rance red marble form the major tones of the decoration. They are combined with complex geometric patterns, such as circular shapes in Trier diabase and Rance red marble, and rhombuses in Fior di Pesco and white marble. These shapes are underlined by straight or curved rods in white marble or Pierre de Meuse, in order to produce a trompe-l’oeil effect. The figurative decorations described above were certainly located in the middle and upper parts of the revetments.Near this luxurious room, another small heated room was explored, from which some decorative elements made in Gris des Ardennes and in Mediterranean marbles were also collected. These are associated with a wall mosaic made of glass paste including 1570 tesserae of various colours, some of which are enhanced with gold leaf.Between these two rooms, a tank and a service room of about 20 m2 were discovered. The remains of a cooking hearth next to the wall adjoining the tank and the presence of animal bones and oysters on the floor, show that this place was also used for culinary activities. The above rooms, tank and service room seem to be part of an apartment within the residence.Therefore, the luxurious room could be considered as a triclinium. Indeed, its almost square shape and its general dimensions are similar to those of the dining rooms of Pompeian houses. This room was overlooking a peristyle courtyard decorated with a Tuscan colonnade carved in Avesnes stone. There was however no direct connection to the baths which were situated in the northern wing of the residence. In contrast to the decoration of the triclinium, most of the stones are set with tile mortar for a better resistance to water damage. The lower parts of the walls were covered with slabs made in Gris des Ardennes, Pierre de Meuse and red Rance marble.Finally, the existence of other decorated rooms in the villa is assumed, based on the presence of hundreds of fragments collected in secondary or unspecified layers. They demonstrate the use of Belgian stones in forms different from those observed in both the southern wing and the baths of the northern wing.